The Influence of the Clean Morning Program on the Environmentally Caring Character of Elementary School Students - Siregar, Nurliana (Jurnal Pendidikan Profesi Guru, 2026)
This study investigates the influence of the Morning Cleanliness Program on the development of environmental care character among elementary school students. As environmental awareness becomes increasingly essential in early education, schools play a critical role in shaping pro-environmental attitudes and habits. This quantitative research employed a pre-experimental one-group pretest–posttest design involving 62 students from a public elementary school. Data were collected through a validated environmental character questionnaire, structured observations, and documentation of student participation in daily cleaning activities. The results indicate a significant improvement in students’ environmental care character after participating in the program, with the mean score increasing from 67.45 in the pretest to 84.92 in the posttest. Observational data also showed greater initiative, responsibility, and consistency in waste management practices and classroom maintenance. These findings suggest that structured daily routines emphasizing collective responsibility can reinforce pro-environmental behavior in young learners. The study highlights the importance of integrating school-based environmental programs into the curriculum to foster long-term ecological awareness. Implications include the need for sustained implementation, teacher modeling, and parental involvement to ensure the internalization of environmental values.